Antike jüdische Bibelübersetzungen als Zeugnis der kulturellen Begegnung - Tilly, Michael 1963- (2015)
This paper presents the question how the LXX transferred its religious message in an entirely different language, thinking and living world and enabled by this tremendous cultural transfer power the deep influence of Hebrew terminology and oriental ideas and imagery on the European languages and cultures.